Alkali-ion Batteries - Yang, Dongfang (IntechOpen, 2016)
This book covers selected topics in different aspects of science and technology of alkali-ion batteries written by experts from international scientific community. Through the 9 chapters, the reader will have access to the most recent research and development findings on alkali-ion batteries through original research studies and literature reviews. This book covers inter-disciplinary aspects of alkali-ion batteries including new progress on material chemistry, micro/nano structural designs, computational and theoretical models and understanding of structural changes during electrochemical processes of alkali-ion batteries.